Talent Analytics System for UMP Lecturer Performance - Wong Weng, Tim (2013)

(untitled)
Talent analytics is a concept of taking effective ways of analysing employee data in order to enhance workforce performance. This concept will be adopted in University Malaysia Pahang (UMP). The currently applied system, E-pat, is an instructional evaluation system that able to evaluate lecturer performance. This system has some limitation in analysing lecturer performance. For instance, in the E-PAT evaluation system, those questions do not group for evaluation of lecturer skills and do not show up any report in response to skills of lecturers. Lecturer could not obtain a clear idea from the E-PAT for their decision making to improve their skills. Hence, this study was aimed to develop a Talent Analytics System (TAS) for analysing of UMP lecturer performance. In this system, the report of lecturer performance was improved in order to help in them identifying skills they need to be improved. In the improved system, the data from E-PAT student evaluation data would be processed into useful data for assisting lecturer in analysing their skills. Along with an investigation of the literature, an idea is taken that E-PAT‘s questions will be divided into 4 groups to determine skills of lecturer such as personality, communication, technical and teaching. In the development, three modules is developed such as lecturer module, faculty module and CAIC module. Each module consists of three function, there are visualize, analyse and generate report. Besides that, information visualization technique will be incorporated into the system so that lecturer can easily understand the report by looking at the presentation graph. In this project interview session was selected to address the requirement for the development of the system. The system was developed using Google tools and some programming language such as PHP and HTML5. Water fall methodology was chosen in this project that incorporated from the starting of the development system to end of the project. At the end of the system development, there were 83% of users satisfied with the TAS.